Perancangan Aplikasi Simpan Pinjam Dengan Menggunakan Framework Enterprise Architecture Planning (EAP) (Study Kasus: KSPPS DTU Syariah) - Aditya Rofy Gilrandy; Sidiq, Maulana; Dwicahya Supriatman, Rian (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
This research aims to create a savings and loan application that can improve operational efficiency and service quality at KSPPS DTU Syariah. By using the EAP framework, the application is expected to speed up the administration process and simplify transactions, especially in savings and loan services. This application automates various processes such as loan applications, loan management, deposit management, and deposit applications, thereby reducing the time and effort required. Apart from that, this application is designed to improve communication between KSPPS DTU Syariah and its members through features that make it easier to access information and services. The research results show that developing savings and loan applications with the EAP framework can bring significant improvements in operational efficiency and cooperative service quality. Additional suggestions for this research are to carry out regular evaluations of the applications that have been implemented to ensure that the applications remain relevant to member needs and support continuous improvement in operational processes and cooperative services.